Improving Knowledge About Breast Cancer In Hemato Oncology Inpatients And Outpatients As An Effort To Find Early Cases At Haji Hospital, East Java Province - Een Hendarsih; Muhammad Naufal Alzaky; Fitri Lailatul Maghfiroh; Radyta Radwa Maudyna; Almira Rahma Fadhila (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2026)
Background: Breast cancer is the cancer with the highest incidence in women both in Indonesia and in the world. According to Globocan 2018 data, the incidence of breast cancer in Indonesia in 2018 was more than 58,000 new cases with the death of more than 22,000 women. The life expectancy of breast cancer patients is highly dependent on the stage, the higher the stage of breast cancer, the lower the life expectancy. Aim: This study aims to increase knowledge about breast cancer in inpatients and outpatients of hemato oncology as an effort to find early cases at Haji Regional Hospital, East Java Province as an effort to detect breast cancer early so as to increase the life expectancy of breast cancer patients. Method: The method used is descriptive analytic with educational delivery using power point presentation media, leaflets then filled out questionnaires before and after education which were then analyzed with Pearson correlation test group pretest-posttest through SPSS program. The study will take place in August 2025. Results: The average posttest score was higher than the pretest score, meaning there was an increase in knowledge about breast cancer after the education.